Blue Crab Agrobusiness Development at Blue Crab Processing Enterprises Group, Pasuruan - Mimit Primyastanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
The aim of this community service was to introduce a new technology of Milk Blue Crab to improve its economic value. The activity was conducted by extension and demonstrating to the small medium enterprises in Pasuruan City. The success of activities was evaluated by qualitative and quantitative analysis. The results showed that the community was interested to try and implement this new technology (smoking cash fish, meat mincer, and grinder machine). However, there were some problems for the small medium enterprises to apply this method, such as inadequate equipment. Therefore, such technology was only conducted by home industry that still cannot extend its market share. Consequently, selling activities cannot operates well. The suggestion from this activity was important to make business partnership between government, entrepreneur and other institutions that has a relation to this activity to increase more society incomes.Keywords: blue crab, bubu net, steamer, sortage table